Quasi-P-Normal and n-Power class Q Composite Multiplication Operators on the Complex Hilbert Space (Global Journal of Science Frontier Research, 2023)
In this paper the condition under which composite multiplication operators on L2 -space become Quasi-P-Normal operators and n-Power class Q operator have been obtained in terms of radon-nikodym derivative f0
Keywords: composite multiplication operator; conditional expectation; Quasi-p-normal; multiplication operator; class Q operator